1997
DOI: 10.1046/j.1471-4159.1997.69010126.x
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Alterations of GABAA Receptor Subunit Peptide Levels in Rat Cortex During Chronic Ethanol Consumption and Withdrawal

Abstract: The pharmacological properties of y-aminobutyric acidA (GABAA) receptors are altered by prolonged exposure to ethanol both in viva and in vitro. We have shown previously that prolonged ethanol exposure elicits selective alterations in various GABAA receptor subunit mRNA levels in rat cerebral cortex. Some of these effects are rapidly reversed during ethanol withdrawal. The present study was conducted to determine the effects of prolonged ethanol exposure (dependence) and ethanol withdrawal on cerebral cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
215
2
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(238 citation statements)
references
References 14 publications
18
215
2
3
Order By: Relevance
“…Cortical peptide levels for β 2/3 and γ 1 and mRNA for γ 2S increase in ethanol-dependent rats (Devaud et al, 1997).…”
Section: Plasticity Of Gaba a Receptor Subunits In Chronic Ethanol Comentioning
confidence: 89%
See 1 more Smart Citation
“…Cortical peptide levels for β 2/3 and γ 1 and mRNA for γ 2S increase in ethanol-dependent rats (Devaud et al, 1997).…”
Section: Plasticity Of Gaba a Receptor Subunits In Chronic Ethanol Comentioning
confidence: 89%
“…In contrast, a consistent finding in rodents is that chronic ethanol consumption decreases cortical mRNA and peptide levels of α 1 subunits but increases α 4 levels (Devaud et al, 1996(Devaud et al, , 1997Grobin et al, 1998;Matthews et al, 1998). Cortical peptide levels for β 2/3 and γ 1 and mRNA for γ 2S increase in ethanol-dependent rats (Devaud et al, 1997).…”
Section: Plasticity Of Gaba a Receptor Subunits In Chronic Ethanol Comentioning
confidence: 97%
“…Northern blot analysis and RT-PCR have both shown that chronic ethanol consumption increases a 4, a6, y', and Y2s mRNA levels (Morrow et al, 1992;Devaud et al, 1995) while decreasing a1 mRNA levels (Montpied et al, 1991;Morrow et al, 1992;Devaud et al, 1995) in the cerebral cortex and cerebellum. Furthermore, alterations in GABAA receptor peptide expression mirror the changes found in mRNA expression following chronic ethanol consumption (Devaud et al, 1997). These results suggest that chronic ethanol exposure may lead to alterations in subunit assembly of GABAA receptors that could mediate the neurochemical and behavioral tolerance to ethanol and the cross-tolerance to benzodiazepines and barbiturates found following chronic ethanol consumption (Devaud et al, 1995(Devaud et al, , 1996(Devaud et al, , 1997Morrow, 1995).…”
mentioning
confidence: 88%
“…Suppression of α 4 expression prevented the response to 1-3 mM ethanol after progesterone withdrawal, further supporting the suggestion that α 4 βδ sub-unit isoforms of the GABA A receptor possess a unique sensitivity to ethanol. It is interesting that ethanol withdrawal also increases expression of the α 4 subunit of the GABA A receptor (Devaud et al, 1997;Mahmoudi et al, 1997), but it decreases expression of the δ subunit of the GABA A receptor (Cagetti et al, 2003), an effect correlated with a decrease in response to ethanol.…”
Section: Introductionmentioning
confidence: 99%